ANALISIS PENGARUH PENERAPAN SISTEM MANAJEMEN SUMBER DAYA PERUSAHAAN (ERP) DALAM MENINGKATKAN KINERJA MANAJEMEN RANTAI PASOK (SCM) PADA PT. TECTRON MANUFACTURING BATAM - Angelina Julia Renaldi; Eni Valentina; Richmond Richmond; Rizni Aulia Qadri; Adi Wilyanto (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
In a large-scale manufacturing company, it certainly requires supply chain managementprocedures that can make it easier to manage its business activities from start to finish. ERPis a flexible system that integrates and manages production activities that can improve theperformance or performance of a company. The author uses a qualitative method in theanalysis of this research, namely by observing, analyzing, and interviewing related to theERP system and the company's SCM performance. The purpose of this analysis is to findout information related to the ERP system used and the performance of supply chainmanagement at PT. Tectron Manufacturing and knowing the influences that occur incompanies when using an ERP system and the process of implementing an ERP system ineach of its departments. In the business process PT. Tectron Manufacturing implements anERP system managed by a director and head engineer. The results of the analysis of theinfluence of the ERP system on the performance of SCM PT. Tectron Manufacturing is aperformance system that becomes more effective and efficient because this company isengaged in manufacturing which requires clear data collection of all raw materials tofinished goods.Keywords: Company, ERP, Manufacturing, Performance, Supply Chain.